The Effect of Liquidity and Leverage Ratios on Profitability in Automotive and Component Sub-Sector Companies on the IDX 2016 - 2020 - Dewi Suci Heryati; Dody Kurniawan (Draf Solusi Indonesia, 2023)
The Effect of Liquidity and Leverage Ratios on Profitability in Automotive and Component Sub-Sector Companies on the IDX in 2016 – 2020. This study aims to determine the effect of Liquidity (Current Ratio) and Leverage (Debt to Equity Ratio) on Profitability (Return On Assets) in Companies Automotive Sub-Sector and Components on the Stock Exchange in 2016 – 2020. The independent variables in this study are Liquidity (Current Ratio), and Leverage (Debt to Equity Ratio). While the dependent variable in this study is Profitability (Return On Assets). The data used in this study is data on the financial statements of companies in the automotive and component sub-sectors on the IDX in 2016 – 2020. The data analysis method in this study uses multiple linear regression analysis. The hypothesis is submitted by statistical tests, namely the F test (simultaneous) and the T test (partial). The results of this study indicate that Liquidity (Current Ratio) has no effect on Profitability (Return On Assets) in the automotive and component sub-sector companies on the IDX in 2016 - 2020. Leverage (Debt to Equity Ratio) has a significant negative effect on Profitability (Return On Assets). in the automotive and component sub-sector companies on the IDX in 2016 - 2020. And based on the results of the F Test in this study, the Liquidity (Current Ratio) and Leverage (Debt to Equity Ratio) variables together (simultaneously) affect Profitability (Return). On Asset) ) in automotive and component sub-sector companies on the IDX in 2016 – 2020. This is evidenced by the calculated value (4.551 > 3.10) with a significance level (0.013 < 0.05).